A novel hanging spherical drop system for the generation of cellular spheroids and high throughput combinatorial drug screening. (21st January 2015) - Neto, A. I.; Correia, C. R.; Oliveira, M. B.; Rial-Hermida, M. I.; Alvarez-Lorenzo, C.; Reis, R. L.; Mano, J. F.
Abstract : A novel hanging spherical drop system based on the use of biomimetic superhydrophobic flat substrates allows one to generate arrays of independent spheroid bodies in a high throughput manner, in order to mimic in vivo tumour models on the lab-on-chip scale. Abstract : We propose a novel hanging spherical drop system for anchoring arrays of droplets of cell suspension based on the use of biomimetic superhydrophobic flat substrates, with controlled positional adhesion and minimum contact with a solid substrate. By facing down the platform, it was possible to generate independent spheroid bodies in a high throughput manner, in order to mimic in vivo tumour models on the lab-on-chip scale. To validate this system for drug screening purposes, the toxicity of the anti-cancer drug doxorubicin in cell spheroids was tested and compared to cells in 2D culture. The advantages presented by this platform, such as feasibility of the system and the ability to control the size uniformity of the spheroid, emphasize its potential to be used as a new low cost toolbox for high-throughput drug screening and in cell or tissue engineering.